BANK CREDIT AND FORESTRY OUTPUT : DO BANKING DEREGULATION AND ECONOMIC CRISIS MATTER? - Muyanja Ssenyonga (Agro Ekonomi, 2004)
The article investigates the effect bank credit extended to the forestry sub-sector to the sub sector's output, and wether banking deregulation and the economic crisis have any impact on such a relationship. research findings shows hat bank credit is found to have positive influence on forestry output. bank credit to the forestry sub-sector, paradoxically continues to rise in the wake of the economic crisis,before it plumments. there is  also evidence of an augmenting effect of banking deregulation on forestry output, proof that deregulation indeed works. the economic crisis however, is found to have led to a tumultuos decline in output as expected. policy implications were drawn basing on research findings.